The origin of financial crises : central banks, credit bubbles and the efficient market fallacy - Cooper, George (Petersfield, Great Britain : Harriman House, 2008)
The book provides concise descriptions of the role of central banking. The author distinguishes among the philosophies of different central bankers, such as between the Federal Reserve and the European Central Bank. According to him financial systems do not behave according to the laws of the efficient market hypothesis but they are inherently unstable with no steady state equilibrium.
Includes bibliographical references and index.
lje 10/9/13
Loans
Keywords: Financial Crises; Efficient market theory; Banks and banking, Central; Monetary policy